The strategic role of lipidomics in biomarker identification and diagnosis of gynecological diseases - Hou, Menghui; Chu, Xinying; Wang, Shuxin; Zhang, Qingyue; Ma, Mingjie; Ma, Jing (Frontiers in Endocrinology, 2025)
Lipidomics, an emerging field in medical research, has deepened our understanding of lipid metabolism, signal transduction pathways, and intercellular communication through qualitative and quantitative analyses of patient lipid profiles. It has closely linked these biological processes to the occurrence and progression of diseases, opening new avenues of research and providing new perspectives on the diagnosis, treatment, and personalized medicine of clinical diseases. Gynecological diseases have a profound impact on women’s health but often face challenges due to delayed diagnosis and inadequate treatment options. Lipids play a crucial role in regulating cell proliferation, differentiation, and signal transduction, making them significant in the occurrence and development of gynecological diseases. The technological progress in lipidomics has greatly advanced our comprehension of lipid metabolism and biochemical mechanisms in these diseases, while also offering new technical pathways for identifying potential biomarkers. Thus, this review summarized the application of lipidomics in gynecological diseases, especially those with high incidence rates such as ovarian cancer, cervical cancer, and endometriosis, to assesses its application potential in the diagnosis, prognosis monitoring, and development of new treatment strategies for gynecological diseases, and discusses its future development trends.